Learning based robotic grasping - Wang, Chongyu (Nanyang Technological University, 2022)
Nowadays, with the rapid development of artificial intelligence, machine learning has made great strides in making computers behave more intelligently. In this context, machine learning has been applied to robots to make them work in a more reasonable way. This has enabled rapid advances in robotic work planning.